2018
DOI: 10.1920/wp.ifs.2018.w1814
|View full text |Cite
|
Sign up to set email alerts
|

Subjective expectations of survival and economic behaviour

Abstract: This paper investigates individuals' expectations about their own survival to older ages and compares patterns in average responses about survival chances with actual and projected survival rates. The extent to which individuals have, on average, accurate expectations about survival to older ages is important in a context of increasing personal responsibility for and control over the accumulation and use of savings for retirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The "50% blip" is a particularly salient form of misreporting of beliefs. Also, recent research found 7 percent of respondents to ELSA reported a 100% probability of living a decade into the future; given risk of accidental death, these 100% responses could be interpreted as evidence that respondents misunderstand the objective probabilities (O'Dea & Sturrock, 2018). As noted above, however, these response patterns could equally be interpreted as support for the Modal Response Hypothesis (Hudomiet & Willis, 2013): in this view, survey researchers are wrongly inferring means from respondents' modes.…”
Section: Section I: Comparing Subjective Life Expectancy Across Countmentioning
confidence: 96%
“…The "50% blip" is a particularly salient form of misreporting of beliefs. Also, recent research found 7 percent of respondents to ELSA reported a 100% probability of living a decade into the future; given risk of accidental death, these 100% responses could be interpreted as evidence that respondents misunderstand the objective probabilities (O'Dea & Sturrock, 2018). As noted above, however, these response patterns could equally be interpreted as support for the Modal Response Hypothesis (Hudomiet & Willis, 2013): in this view, survey researchers are wrongly inferring means from respondents' modes.…”
Section: Section I: Comparing Subjective Life Expectancy Across Countmentioning
confidence: 96%
“…; Bozio et al . ; Crawford and Sturrock ; O'Dea and Sturrock , ). In a recent paper, they endorse the life expectancy information on the US Social Security web page as a means to attenuate the bias against annuities, and advocate a ‘role for larger policy interventions to inform households about the length of the retirement that they might have to fund’ (O'Dea and Sturrock , p. 20).…”
Section: Discussionmentioning
confidence: 99%
“…There is a robust finding in the literature on subjective life expectancy that younger people underestimate their life expectancy, but that this tendency reduces with age; this pattern has been reported for the USA (Elder ), Australia (Wu et al . ) and the UK (O'Dea and Sturrock ). This downward bias in anticipated lifespan has been hypothesized to explain part of the annuities puzzle (O'Dea and Sturrock ).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It is potentially the case that it is not only actual mortality risk which is important for employment, but perceived mortality risk as well. Evidence from the UK in O'Dea and Sturrock (2018) indicates that people are aware that various risk factors, such as smoking and early death of parents, shorten life expectancy, suggesting that it is likely people will adjust their life expectancy in response to shocks to their health. However, this paper highlights a crucial issue in the UK that should concern policymakers.…”
Section: Pathways For Health To Affect Retirementmentioning
confidence: 99%